Assessing Urban Vitality: A checklist assessment method for evaluating high street success and public space quality in medium-size English towns - Yusra Ali; Ahmad Taki (International Journal of Urban Sustainable Development)
UK High Streets, long central to urban life, face increasing uncertainty due to shifts in retail. Public spaces are crucial to high streets and town centres, connecting the activities within and around them. As part of broader research investigating the role of public space in high street vitality, this paper proposes a checklist assessment method to evaluate high street success alongside public space quality, drawing upon findings from relevant literature. This study employs a case study approach, analysing data from four medium-sized towns in the Midlands, England. The research conducted using this checklist method demonstrates results consistent with the literature, indicating a positive interdependency between high street success and public space quality, making it a reliable tool for assessing urban vitality.